Good governance and international relations in Iranian sports organizations - Rassouli, M.; Sajjadi, N.; Mosaffa, N.; Rasekh, N. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2020)
This study aimed to analyze good governance (GG) and international relations in Iranian sports organizations. The sample was composed of 150 sport managers from Iran. The instrument used was an ad hoc questionnaire based on the basic universal principles of GG of the Olympic and Sports Movement. The validity and reliability of the questionnaire were confirmed. After data collection, the data were analyzed with IBM SPSS Amos 23, using descriptive and inferential statistical methods. According to the Iranian sports managers that participated in this study, the most important factors of GG and international relations in Iranian sports organizations were, in order of importance: Internal integrity and independency, transparency, responsibility, discipline, accountability, rule of law, participation and democracy.